Correction to: Perspectives and pregnancy outcomes of maternal Ramadan fasting in the second trimester of pregnancy - Kolsoom Safari; Tiran Jamil Piro; Hamdia Mirkhan Ahmad (BMC, 2019)
Following publication of the original article [1], the author notified us about the incorrect values on Table 4.